Creating an evidence map of the safety profile of spironolactone across all clinical indications to establish whether it may be a safe treatment in female adolescent acne: a protocol for a scoping review - Esther Burden-Teh; Myranda Attard; James Law; Zahra Moledina; Susannah George; Fiona C Sexton; Lisa O’Higgins; Julia Fordham; Grishma Ramesh (BMJ Open)
Introduction Spironolactone is a useful and effective acne treatment option for adult female patients. We aim to establish whether spironolactone could be a safe treatment for the management of acne in the female adolescent population as well. The objective of this scoping review is to provide an evidence map of the safety profile of spironolactone in the paediatric population aged 0–17 across all clinical indications.Methods and analysis This scoping review will be conducted according to the Joanna Briggs Institute scoping review protocol. Relevant publications will be searched on the MEDLINE, Embase and Web of Science databases from inception until July 2025. The authors of included studies will be contacted using contact details provided in the manuscript to check for any further published or unpublished data on the review question. An initial search will be conducted using keywords to identify relevant articles. After identifying the research strategy, articles will be extracted into a reference management tool, and a two-part study selection process will be systematically applied by two reviewers. The first part consists of screening titles and abstracts to define the eligibility of each article. In the second part, the full texts will be screened and only relevant articles will be kept. All articles related to the safety of spironolactone in children and adolescents across all clinical indications will be included. Data will be extracted using a scoping review management software such as Covidence, collated and charted to summarise all the relevant methods, outcomes and key findings in the articles.Ethics and dissemination This scoping review will provide an extensive overview of the available safety evidence for the use of spironolactone in children and teenagers. Since the scoping review methodology consists of reviewing and collecting data from publicly available materials, this study does not require ethics approval. The results will be disseminated in a peer-reviewed publication.